Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22179596
|View full text |Cite
|
Sign up to set email alerts
|

Metal and Metal Oxide Nanoparticle as a Novel Antibiotic Carrier for the Direct Delivery of Antibiotics

Abstract: In addition to the benefits, increasing the constant need for antibiotics has resulted in the development of antibiotic bacterial resistance over time. Antibiotic tolerance mainly evolves in these bacteria through efflux pumps and biofilms. Leading to its modern and profitable uses, emerging nanotechnology is a significant field of research that is considered as the most important scientific breakthrough in recent years. Metal nanoparticles as nanocarriers are currently attracting a lot of interest from scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 90 publications
0
46
0
Order By: Relevance
“…Biofabricated CuO-NPs have gained interest as an antibacterial therapy due to their unique morphologies, diameters, and biocompatibility. A type of CuO-NPs is antimicrobial, working against both Gram-positive and Gram-negative bacteria. , Previous studies have shown that the antibacterial property of CuO-NPs is produced through a green method utilizing the Tabernaemontana divaricata leaf extract and shown against Helicobacter pylori …”
Section: Resultsmentioning
confidence: 99%
“…Biofabricated CuO-NPs have gained interest as an antibacterial therapy due to their unique morphologies, diameters, and biocompatibility. A type of CuO-NPs is antimicrobial, working against both Gram-positive and Gram-negative bacteria. , Previous studies have shown that the antibacterial property of CuO-NPs is produced through a green method utilizing the Tabernaemontana divaricata leaf extract and shown against Helicobacter pylori …”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 /ZnO nanoparticles have a more pronounced bactericidal effect against E. coli compared to ZnO nanoparticles, while Ag/TiO 2 /ZnO nanoparticles are more effective than TiO 2 /ZnO nanoparticles [ 132 ].…”
Section: Complex Inpsmentioning
confidence: 99%
“…However, INPs have significant potential not only as effective antibacterial components of drugs, but also as possible carriers of next-generation drugs providing targeted delivery and controlled release into diseased tissue. When studying the antibacterial properties of such hybrid systems of antibacterial drugs, it emerged that they are characterized not only by their expansion of the spectrum of action, but also by the mutual enhancement of the antibacterial activities of INPs and antibiotics [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…This is to reduce the loss of metal-containing NPs and NP amount and their activities in blood circulation besides minimizing damage to host cells and tissue [ 104 ]. Conjugation of existing antibiotics with highly targeted metal-containing NPs helps to selectively capture and kill MRSA by overloading defenses of drug-resistant bacteria [ 105 ]. A study from Wang and colleagues stated that target-oriented photo-functional NPs which are conjugated with both hematoporphyrin and monoclonal MRSA antibody killed selectively MRSA in L-929 cells [ 106 ].…”
Section: Challenges In Using Metal-containing Nps In Treating Mrsamentioning
confidence: 99%